1998
DOI: 10.1002/hep.510280418
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin-induced disruption of actin cytoskeletal organization and canalicular function in isolated rat hepatocyte couplets: Possible involvement of protein kinase C

Abstract: The effect of vasopressin (VP) on canalicular function and hepatocellular morphology, with particular regard to actin cytoskeletal organization and the concomitant plasma membrane bleb formation, was studied in isolated rat hepatocyte couplets. VP induced the concentration-dependent formation of multiple plasma membrane blebs as well as simultaneous impairment in both canalicular vacuolar accumulation (cVA) and retention (cVR) of the fluorescent bile acid, cholyl-lysyl-fluorescein (CLF), which evaluate couplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…It is well known that some GPCR ligands, such as LPA, S1P, and thrombin, also induce contractive actin bundles in cells (Miller et al 2012;Mo et al 2012;Yu et al 2012b). On the other hand, some ligands for Ga s -coupled receptors, such as vasopressin, dopamine, and parathyroid hormone, have been shown to counteract the formation of actin bundles (Ding et al 1991;Egan et al 1991b;Roma et al 1998;Nguyen et al 1999;Zhang et al 2006). Mechanical cues such as cell spreading, cell geometry, and matrix stiffness all result in rearrangement of the actin cytoskeleton (Dupont et al 2011;Wada et al 2011;Zhao et al 2012).…”
Section: Extracellular Matrix (Ecm) and Cytoskeleton: Sensing Mechanimentioning
confidence: 99%
“…It is well known that some GPCR ligands, such as LPA, S1P, and thrombin, also induce contractive actin bundles in cells (Miller et al 2012;Mo et al 2012;Yu et al 2012b). On the other hand, some ligands for Ga s -coupled receptors, such as vasopressin, dopamine, and parathyroid hormone, have been shown to counteract the formation of actin bundles (Ding et al 1991;Egan et al 1991b;Roma et al 1998;Nguyen et al 1999;Zhang et al 2006). Mechanical cues such as cell spreading, cell geometry, and matrix stiffness all result in rearrangement of the actin cytoskeleton (Dupont et al 2011;Wada et al 2011;Zhao et al 2012).…”
Section: Extracellular Matrix (Ecm) and Cytoskeleton: Sensing Mechanimentioning
confidence: 99%
“…Therefore, an increase in cytosolic calcium by norepinephrine induces contraction of bile canaliculi in the doublet hepatocytes; the contraction is inhibited by wortmannin [7]. It has also been reported that vasopressin induced the disruption of actin cytoskeletal organization and canalicular function either via protein kinase C activation or calcium mobilization [26]. It has been reported that bile canalicular peristalsis is propagated by pericentral to periportal calcium waves via gap junctions, through which second messengers communicate between hepatocytes [8, 27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, insulin stimulates phosphatidylinositol 3-kinase (PI3K) activity in rat [67] and inhibits secretin-induced ductal secretion by activation of PKCa and inhibition of PKA activity [68]. In hepatocyte couplets vasopressin induces canalicular and cytoskeletal dysfunction that is probably mediated by PKC and intracellular Ca 2+ [69]. Stimulation of ATP receptors induces Ca 2+ signalling in bileduct epithelia [70] and angiotensin II activates a signalling pathway leading to phosphorylation of MAPK in hepatocytes; this event is mediated by a CaM-dependent protein kinase, a PKC-dependent pathway and a PI3K-dependent pathway [71].…”
Section: Short-term Regulation Of Octsmentioning
confidence: 99%